Multimodality instructions in teaching reading using multimodal texts: Its impact on students’ semiotic awareness - Ngadiso Ngadiso; Kristiandi Kristiandi; Herlina Usman (Universitas Syiah Kuala, 2026)
This study investigates students’ responses to the implementation of multimodality instructions in teaching reading using multimodal texts and their impact on students’ development of semiotic awareness. This study employed a two-cycle classroom action research design, each of which consisted of planning, acting, observing, and reflecting. The participants involved in this study were 42 third-semester students majoring in English Education enrolling in a reading class. The data were collected using observation, a questionnaire, and interviews. The observation and interview data, as well as the theme emerging from the questionnaire data, were analyzed using an interactive model of analysis consisting of data condensation, data display, and conclusion drawing/verification. The study found that the students had a positive response toward the lecturer’s multimodality instructions in teaching reading using multimodal texts. The four strategies used in employing multimodality instructions in teaching reading using multimodal texts, namely assessing students’ knowledge of semiotics, helping students use their knowledge of semiotics to build mental pictures, guiding students to use background experience in using linguistic knowledge to make predictions, and guiding students to confirm predictions enabled students to construct mental pictures, influence semiotic knowledge, and utilize background experience to facilitate reading comprehension. These strategies were also found to help develop students’ semiotic awareness, which included visual, linguistic, and multimodal awareness. The findings stress the importance of multimodality instructions in reading pedagogy, particularly to nurture semiotic awareness and enhance reading comprehension. This implies that multimodality instructions using multimodal texts can be beneficial for promoting better literacy skills.